2014
DOI: 10.1074/jbc.m113.512749
|View full text |Cite|
|
Sign up to set email alerts
|

First Evidence for a Covalent Linkage between Enterobacterial Common Antigen and Lipopolysaccharide in Shigella sonnei Phase II ECALPS

Abstract: Background: Enterobacterial common antigen (ECA) is a surface antigen of all enteric bacteria. Results: ECA polysaccharide substitutes the outer core region of Shigella sonnei lipopolysaccharide (LPS). Conclusion: First structural evidence for the existence of ECA covalently associated with LPS (ECA LPS ). Significance: ECA LPS is the only immunogenic form of ECA and could be a target for therapeutic strategies against nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…Since repeating units of both polymers are assembled on the same lipid carrier—undecaprenyl pyrophosphate (Und-PP)—and undergone similar processing [ 25 ], key features of ECA LPS structures are predicted partially on the basis of biosynthesis pathway analyses: (i) ECA LPS can only be observed in strains incapable of producing the O-PS [ 3 , 25 ]; (ii) ECA is ligated to the core OS in the position used to be occupied by O-PS, and (iii) an inverted anomeric configuration of the D-Glc p NAc residue in the first ECA repeating unit linked to the core OS has to be observed, whereas an α-configuration is a characteristic for polymeric chain ( Figure 1 ) [ 3 ]. All these presumptions were positively verified by our single case study on S. sonnei phase II ECA LPS [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Since repeating units of both polymers are assembled on the same lipid carrier—undecaprenyl pyrophosphate (Und-PP)—and undergone similar processing [ 25 ], key features of ECA LPS structures are predicted partially on the basis of biosynthesis pathway analyses: (i) ECA LPS can only be observed in strains incapable of producing the O-PS [ 3 , 25 ]; (ii) ECA is ligated to the core OS in the position used to be occupied by O-PS, and (iii) an inverted anomeric configuration of the D-Glc p NAc residue in the first ECA repeating unit linked to the core OS has to be observed, whereas an α-configuration is a characteristic for polymeric chain ( Figure 1 ) [ 3 ]. All these presumptions were positively verified by our single case study on S. sonnei phase II ECA LPS [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 52%
“…Even though the existence and immunogenicity of ECA LPS were suggested in the 1960s by Kunin et al [ 5 , 6 ], it was relatively recent studies that demonstrated the first example of the covalent linkage between ECA and LPS in rough Shigella sonnei phase II [ 7 , 8 ]. Rough form of S. sonnei LPS, lipooligosaccharide (LOS) devoid of the O-PS, was partially substituted by ECA at the position occupied by the O-PS in the case of smooth S. sonnei phase I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this finding, we presume that Wzz fepE has a novel role during L-OAg biosynthesis in the absence of VisP via cross-complementation. Recently, enterobacterial common antigen (ECA) was first characterized in Shigella sonnei as linked to LPS (more specifically, to lipid A) anchored to the OM (108). Therefore, the L-OAg modality observed here in the absence of Wzz ST in the ΔvisP wzz ST strain may be ECA LPS chains with similar lengths of L-OAg.…”
Section: Discussionmentioning
confidence: 79%
“…It consists of linear repetitive units of a trisaccharide composed of 4-acetamide-4,6-dideoxy-D-galactose (Fuc4NAc), N-acetyl-D-mannosaminuronic acid (ManNAcA), and N-acetyl-D-glucosamine (GlcNAc). It is considered the second dominant immunogen, ranked next to the lipopolysaccharide (LPS) O-antigen [3,5,6]. Three ECA variants, ECA PG , ECA LPS and ECA CYC , have been described since it was rst found in E. coli [3].…”
Section: Introductionmentioning
confidence: 99%